THE INDONESIAN GOVERNMENT’S LEGITIMATION TOWARD OMNIBUS LAW ON JOB CREATION: A CRITICAL DISCOURSE ANALYSIS STUDY - Rizki Ananda; Nurmainiati (Getsempena English Education Journal, 2022)
Omnibus law on Job Creation passed in 2021 by the Indonesian Government has sparked a nationwide protests from many elements of societies. In this case, with its positive belief in the law, the government has to legitimize it so that it obtains approval from the society. This study seeks to answer the legitimation strategies employed by the government to convice the societies regarding the positive sides of this law implementation. To attain its objective, the current study used qualitative approach with critical discourse analysis as its method and Leeuwen’s framework on legitimation strategies as its analytical toolkit. The data was obtained from five giant online newspapers, namely The Jakarta Post, Serambi Indonesia, Kompas, CNN, and Republika from which 14 articles related to UU Cipker were extracted by means of Google search engine. The result of data analysis reveals that the government employed the moral evaluation strategy, rationalization strategy, and authorization strategy. Out of the three strategies, moral evaluation which is a legitimation built by referring to various moral values, was employed dominantly. Finally, this study suggests the society to critically listen to, read, and understand the government’s language. This study can also be used as a reference by English teachers to legitimize each material presented to motivate their students to be life-long learners by telling them why they should learn those presented materials.